High-hardness and high-conductivity copper alloy composition and process design method, storage medium and equipment

By establishing the thermodynamic database of Cu-Ni-Si-Co copper alloy and using thermodynamic calculation to optimize components and process parameters, the problems of high design cost of copper alloys and the constraints of hardness and conductivity are solved, and a high-efficiency and low-cost high-hard and high-conductive copper alloy design is achieved.

CN119418806BActive Publication Date: 2025-03-18CENT SOUTH UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411896420.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-03-18
Estimated Expiration
2044-12-23

AI Technical Summary

Technical Problem

In the prior art, experimental methods are used to design copper alloy composition and process problems with high cost and long cycles, and there is a mutually restrictive constraint relationship between hardness and conductivity in copper alloys.

Method used

By establishing a thermodynamic database of quadruple Cu-Ni-Si-Co copper alloy, using Pandat software for thermodynamic calculations, combining the open source library pymoo to find Pareto frontiers, optimize the composition and process parameters of copper alloys to achieve high hardness and high conductance copper alloy design.

Benefits of technology

It has achieved efficient design of Cu-Ni-Si-Co copper alloys with high hardness and high conductivity, reducing the blindness and cost of material design and shortening the design cycle.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119418806B_ABST
    Figure CN119418806B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of multi-component copper alloy design, and specifically to a method, storage medium and device for designing the composition and process of a high-hardness and high-conductivity copper alloy. The method comprises establishing a quaternary system thermodynamic database; using Pandat software to calculate and obtain microstructure data that varies with Co content at different aging temperatures; using the open source library pymoo to find the Pareto front of the precipitate phase fraction and the solid solubility of Cu atoms; and using aging experiments to determine the target aging time. The storage medium stores computer program instructions, and the method is implemented when the computer program instructions are executed by a processor. The device comprises at least one processor, at least one memory and computer program instructions stored in the memory, and the method is implemented when the computer program instructions are executed by the processor. The present invention can efficiently realize the composition and process design of a high-hardness and high-conductivity copper alloy, and can break through the constraint relationship between the hardness and conductivity of copper alloy materials that restrict each other.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of multi-component copper alloy design, and in particular to a high-hardness and high-conductivity copper alloy composition and process design method, storage medium and equipment. Background Art

[0002] Cu-Ni-Si copper alloy is widely used in integrated circuit lead frames due to its excellent performance. It is a high-hardness and high-conductivity copper-based material with broad application prospects. However, there is a certain restrictive relationship between hardness and conductivity in copper alloys. Specifically, the content of solid solution strengthening elements in copper alloys is closely related to the hardness of the alloy, but the increase in the solid solubility of the copper alloy matrix phase will increase electron scattering and reduce the conductivity. The contradictory relationship between hardness and conductivity limits the further development and application of copper alloys.

[0003] At present, most of the research reports on the development of copper alloy materials are based on experimental methods, which require the control of alloying elements, addition amounts, and heat treatment processes by relying on expert experience. The design of copper alloys using experimental methods is costly, time-consuming, blind, and inefficient. How to efficiently achieve the design of composition and process and break through the mutually restrictive relationship between the hardness and conductivity of copper alloy materials is an important problem in the current design and development of high-hardness and high-conductivity copper alloys.

[0004] In summary, it is necessary to develop a high-hardness and high-conductivity copper alloy composition and process design method, storage medium and equipment to solve the problems of high cost and long cycle in the prior art of using experimental methods for copper alloy composition and process design, and on the other hand to solve the problem of the restrictive relationship between hardness and conductivity in copper alloys. Summary of the invention

[0005] The present invention aims to provide a high-hardness and high-conductivity copper alloy composition and process design method, storage medium and equipment. The specific technical scheme is as follows:

[0006] In a first aspect, the present invention provides a high-hardness and high-conductivity copper alloy composition and process design method, comprising:

[0007] Step S1, establishing a thermodynamic database of quaternary Cu-Ni-Si-Co copper alloy;

[0008] Step S2, on the basis of selecting Cu-Ni-Si commercial copper alloy, controlling the Cu content to decrease and adding the Co content, or controlling the Ni content to decrease and adding the Co content, based on the thermodynamic database, using Pandat software to calculate and obtain microstructure data that changes with the Co content at different aging temperatures; the microstructure data includes the precipitated phase fraction and the solid solubility of Cu atoms;

[0009] Step S3, using the open source library pymoo to find the Pareto front of the precipitate phase fraction and the solid solubility of Cu atoms, so as to obtain the target content of the copper alloy component; at the same time, selecting the target aging temperature;

[0010] Step S4: Based on the target content of the copper alloy components and the target aging temperature obtained in step S3, an aging experiment is performed to study the effects of different aging times on the hardness and electrical conductivity of the copper alloy, and then the target aging time is determined.

[0011] Optionally, in step S1, the thermodynamic database includes pure component thermodynamic data, binary system thermodynamic data and ternary system thermodynamic data; the pure component thermodynamic data include pure component Cu thermodynamic data, pure component Ni thermodynamic data, pure component Si thermodynamic data and pure component Co thermodynamic data; the binary system thermodynamic data include binary Cu-Ni thermodynamic data, binary Cu-Co thermodynamic data, binary Cu-Si thermodynamic data, binary Co-Ni thermodynamic data, binary Co-Si thermodynamic data and binary Ni-Si thermodynamic data; the ternary system thermodynamic data include ternary Cu-Ni-Si thermodynamic data, ternary Cu-Co-Si thermodynamic data and ternary Cu-Co-Ni thermodynamic data.

[0012] Optionally, in step S2, the Cu—Ni—Si commercial copper alloy includes C70260 commercial copper alloy.

[0013] Optionally, in step S2, the added Co content is controlled to be added to a maximum of 2 wt%; at each aging temperature, the added Co content is controlled to have an addition gradient of 0.005 wt%-0.02 wt%.

[0014] Optionally, in step S2, the aging temperature ranges from 200-600°C.

[0015] Optionally, in step S3, the target content of the copper alloy component is as follows:

[0016] 99.3wt%~95.9wt%Cu-0.5wt%~2.5wt%Ni-0.1wt%~0.6wt%Si-0.1wt%~1.0wt%Co.

[0017] Optionally, in step S3, the target aging temperature is in the range of 350-600°C.

[0018] Optionally, in step S4, the target aging time is 1-12 hours.

[0019] The target content of the copper alloy component at the target aging temperature and the target aging time has a Vickers hardness (HV) of 173-235 HV and an electrical conductivity of 35-47% IACS, and has both high hardness and high conductivity properties.

[0020] In a second aspect, the present invention provides a storage medium having computer program instructions stored thereon, which, when executed by a processor, implement the high-hardness and high-conductivity copper alloy composition and process design method.

[0021] In a third aspect, the present invention provides a device comprising: at least one processor, at least one memory, and computer program instructions stored in the memory, which implement the high-hardness and high-conductivity copper alloy composition and process design method when the computer program instructions are executed by the processor.

[0022] The application of the technical solution of the present invention has at least the following beneficial effects:

[0023] The present invention provides a high-hardness and high-conductivity copper alloy composition and process design method, storage medium and equipment, which can not only efficiently realize the high-hardness and high-conductivity copper alloy composition and process design, but also break through the mutually restrictive constraint relationship between the hardness and conductivity of copper alloy materials. Specifically, the present invention adopts step S1 to establish a thermodynamic database of a quaternary Cu-Ni-Si-Co copper alloy; in step S2, the thermodynamic calculation function of Pandat software is used to calculate the effect of adding different Co contents on the solid solubility of Cu in the commercial copper alloy matrix phase, so as to qualitatively explore the level of electrical conductivity; wherein, the greater the solid solubility of Cu, the higher the electrical conductivity of the copper alloy; the thermodynamic calculation function of Pandat software is used to calculate the effect of adding different Co contents on the precipitate phase fraction, so as to qualitatively explore the level of hardness of the copper alloy; wherein, the higher the precipitate phase fraction, the higher the hardness of the copper alloy; in step S3, the open source library pymoo is used to find the Pareto front of the precipitate phase fraction and the solid solubility of Cu atoms, and the target content of the copper alloy composition is obtained, so as to realize the efficient design of the high-hardness and high-conductivity copper alloy composition; at the same time, the target aging temperature is selected in combination with step S3, and the target aging time is determined in combination with step S4, so as to realize the efficient design of the high-hardness and high-conductivity copper alloy process. The present invention adopts steps S1-S4, makes full use of the thermodynamic database and mature thermodynamic calculation technology, does not need to conduct a large number of experimental trial and error, reduces the blindness of material design, and can efficiently and quickly design a Cu-Ni-Si-Co alloy with high hardness and conductivity. In addition, compared with the experimental method in the prior art, the method provided by the present invention not only has the advantages of shortened cycle, simple and fast process and strong operability, but also has high application value.

[0024] In addition to the above-described purposes, features and advantages, the present invention has other purposes, features and advantages. The present invention will be further described in detail with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] The drawings constituting a part of this application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:

[0026] Figure 1 It is an isothermal cross-sectional diagram constructed on the ternary system Cu-Co-Ni based on the thermodynamic database in Example 1 according to Document 1;

[0027] Figure 2 It is a vertical cross-sectional view on the ternary system Cu-Co-Si constructed from the thermodynamic database in Example 1 according to Document 2;

[0028] Figure 3 It is a vertical cross-sectional diagram on the ternary system Cu-Ni-Si constructed from the thermodynamic database in Example 1 according to Documents 3 to 5;

[0029] Figure 4 This is a diagram showing the extrapolation experimental verification results based on the thermodynamic database in Example 1 constructed on a quaternary Cu-1.48wt%Ni-0.5wt%Si-0.52wt%Co copper alloy;

[0030] Figure 5 The trend of the change of the precipitate phase fraction and the solid solubility of copper atoms with the Co content at different aging temperatures by adding Co content to control the reduction of Cu content in Example 1;

[0031] Figure 6 for Figure 5 The trend of the precipitate phase fraction and the solid solubility of copper atoms with Co content at the intermediate aging temperature of 500℃;

[0032] Figure 7 for Figure 5 The trend of the precipitate phase fraction and the solid solubility of copper atoms with Co content at the intermediate aging temperature of 350℃;

[0033] Figure 8 The trend of the change of the precipitate phase fraction and the solid solubility of copper atoms with the Co content at different aging temperatures by adding Co content to control the reduction of Ni content in Example 3;

[0034] Fig. 9 for Figure 8 The trend of the precipitate phase fraction and the solid solubility of copper atoms with Co content at the intermediate aging temperature of 500℃;

[0035] Fig.10 for Figure 8 The trend of the precipitate phase fraction and the solid solubility of copper atoms with Co content at the intermediate aging temperature of 350℃;

[0036] Among them, Figure 1-Figure 3 and Figure 4 In the figure, FCC represents the phase organization of face-centered cubic structure; Liquid represents the liquid phase;

[0037] exist Figure 1 In the formula, x(Cu) represents the atomic fraction of copper; x(Co) represents the atomic fraction of cobalt; x(Ni) represents the atomic fraction of nickel;

[0038] exist Figure 2 In the figure, FCC+Co2Si represents a two-phase region composed of a face-centered cubic phase structure and a compound Co2Si phase; Solidus represents a solidus; "Co2Si, %" represents a phase structure composed of the compound Co2Si;

[0039] exist Figure 3 In the figure, FCC+Ni5Si2 represents a two-phase region composed of a face-centered cubic structure and a compound Ni5Si2 phase; γ(Cu 56 Si 11 )+FCC represents γ(Cu 56 Si 11 ) phase and the phase organization of the face-centered cubic structure; Arrest represents the phase transition point measured experimentally; 1-phase represents the single-phase region, that is, the phase region with only one phase organization; 2-phase represents the two-phase region, that is, the phase region with two phase organizations; 3-phase represents the three-phase region, that is, the phase region with three phase organizations;

[0040] exist Figure 4 In the graph, FCC+(Ni, Co)2Si represents a two-phase region composed of a face-centered cubic structure and a compound (Ni, Co)2Si phase;

[0041] exist Figure 6-Figure 7 as well as Figure 9-10 In the equation, Pareto points represent the points on the Pareto front. DETAILED DESCRIPTION

[0042] The following will be combined with the accompanying drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field belong to the scope of protection of the present invention.

[0043] Embodiment 1:

[0044] High-hardness and high-conductivity copper alloy composition and process design methods, including:

[0045] Step S1, establishing a thermodynamic database of quaternary Cu-Ni-Si-Co copper alloy;

[0046] In step S1, the thermodynamic database includes pure component thermodynamic data, binary system thermodynamic data and ternary system thermodynamic data;

[0047] The pure component thermodynamic data include pure component Cu thermodynamic data, pure component Ni thermodynamic data, pure component Si thermodynamic data and pure component Co thermodynamic data; wherein the pure component thermodynamic data is obtained from the website “https: / / www.sgte.net / en / ”;

[0048] The binary system thermodynamic data include binary system Cu-Ni thermodynamic data, binary system Cu-Co thermodynamic data, binary system Cu-Si thermodynamic data, binary system Co-Ni thermodynamic data, binary system Co-Si thermodynamic data and binary system Ni-Si thermodynamic data;

[0049] The thermodynamic data of the binary Cu-Ni system was obtained from the literature “an Mey S. Thermodynamic re-evaluation of the Cu-Ni system. Calphad 1992;16:255–60.”; see the website “https: / / doi.org / 10.1016 / 0364-5916(92)90022-P”;

[0050] Thermodynamic data of binary Cu-Co system were obtained from the literature “Palumbo M, Curiotto S, Battezzati L. Thermodynamic analysis of the stable and metastable Co–Cu and Co–Cu–Fe phase diagrams. Calphad 2006; 30: 171–8.”; see the website “https: / / doi.org / 10.1016 / j.calphad.2005.10.007”;

[0051] Thermodynamic data of binary Cu-Si system were obtained from the literature “Yan X, Chang Y. A thermodynamic analysis of the Cu–Si system. J Alloy Compd 2000;308:221–9.”; see the website “https: / / doi.org / 10.1016 / S0925-8388(00)00983-X”;

[0052] Thermodynamic data of binary Co-Ni system were obtained from the literature “Fernändez Guillermet A. Assessment of the Thermodynamic Properties of the Ni-Co System. Int J Mater 1987;78:639–47.”; see the website “https: / / doi.org / 10.1515 / ijmr-1987-780905”;

[0053] Thermodynamic data of binary Co-Si system were obtained from the literature “Zhang L, Du Y, Xu H, Pan Z. Experimental investigation and thermodynamic description of the Co–Si system. Calphad 2006; 30: 470–81.”; see the website “https: / / doi.org / 10.1016 / j.calphad.2006.06.001”;

[0054] The thermodynamic data of the binary Ni-Si system was obtained from the literature “Miettinen J. Thermodynamic description of the Cu–Ni–Si system in the copper-rich corner above 700℃. Calphad 2005;29:212–21.”; see the website “https: / / doi.org / 10.1016 / j.calphad.2005.08.001”.

[0055] The ternary system thermodynamic data include ternary system Cu-Ni-Si thermodynamic data, ternary system Cu-Co-Si thermodynamic data and ternary system Cu-Co-Ni thermodynamic data;

[0056] The thermodynamic data of the ternary Cu-Ni-Si system was obtained from the literature “Miettinen J. Thermodynamic description of the Cu–Ni–Si system in the copper-rich corner above 700℃. Calphad 2005;29:212–21. ”; see the website “https: / / doi.org / 10.1016 / j.calphad.2005.08.001”;

[0057] Thermodynamic data of the ternary Cu-Co-Si system were obtained from the literature “Tang Y, Zhang B, Zhong J, Xiong C, CaiJ, Wu X, et al. Development of atomic mobility with quantified uncertaintiesdirectly from concentration profiles: a demo in fcc Cu–Ni–Sn system. J MaterSci 2022;57:3757–76.”; see the website “https: / / doi.org / 10.1007 / s10853-021-06823-z”;

[0058] Thermodynamic data of the ternary Cu-Co-Ni system were obtained from the literature “Curiotto S, Battezzati L, Johnson E,Pryds N. Thermodynamics and mechanism of demixing in undercooled Cu–Co–Nialloys. Acta Mater 2007;55:6642–50.”; see the website “https: / / doi.org / 10.1016 / j.actamat.2007.08.019”.

[0059] The obtained pure component thermodynamic data, binary system thermodynamic data and ternary system thermodynamic data are stored in the .tdb format file commonly used in current thermodynamic calculations, and a thermodynamic database of the quaternary Cu-Ni-Si-Co copper alloy is established.

[0060] In order to verify the accuracy and good extrapolation performance of the thermodynamic database for the quaternary Cu-Ni-Si-Co copper alloy established in step S1, the phase boundary information obtained from literature data or experimental data is used to compare and verify the phase boundary information calculated using the thermodynamic database. The calculation results of the ternary system (see Figure 1-Figure 3 ) is consistent with the phase boundary information reported in the literature (see references 1 to 5); see Figure 4 , the calculation results of the quaternary system (see Figure 4 Calculatedresult in ) and the phase transformation information of the quaternary copper alloy measured by differential scanning calorimetry on the vertical cross section (see Figure 4 This shows that the established thermodynamic database has accuracy and good extrapolation performance.

[0061] Figure 1 This is consistent with the phase boundary information reported in reference 1; reference 1 is “Hasebe M, Oikawa K, NishizawaT. Computer Calculation of Phase Diagrams of Co-Cu-Mn and Co-Cu-Ni Systems. JJpn Inst Met 1982;46:584–90.”; see the website “https: / / doi.org / 10.2320 / jinstmet1952.46.6_584”.

[0062] Figure 2 This is consistent with the phase boundary information reported in Reference 2; Reference 2 is “Takeuchi H, Toda T. On Copper-Side Phase Diagram and Precipitation Hardening Properties of Cu-Co2Si Alloys. J Jpn Inst Met 1962;26:570–5.”; see the website “https: / / doi.org / 10.2320 / jinstmet1952.26.9_570”.

[0063] Figure 3 This is consistent with the phase boundary information reported in References 3 to 5;

[0064] Reference 3 is “Okamoto M. The Investigation of the Equilibrium State of the Ternary Whole System Copper-Nickel-Silicon. III. J Jpn Inst Met 1939;3:365–402.”; see the website “https: / / doi.org / 10.2320 / jinstmet1937.3.10_365”;

[0065] Reference 4 is “Okamoto M. The Investigation of the Equilibrium State of the Whole Ternary System Copper-Nickel-Silicon. J Jpn Inst Met 1939;3:411–20.”; see the website “https: / / doi.org / 10.2320 / jinstmet1937.3.11_411”;

[0066] Reference 5 is “Okamoto M. The Investigation of the Equilibrium State of the Whole System Copper-Nickel-Silicon. J Jpn Inst Met 1938;2:211–32.”; see the website “https: / / doi.org / 10.2320 / jinstmet1937.2.5_211”.

[0067] Step S2, based on the selection of Cu-Ni-Si commercial copper alloy (C70260 commercial copper alloy, composition is 97.5wt%Cu-2wt%Ni-0.5wt%Si), the Cu content is reduced and the Co content is added, see Figure 6-Figure 7 , based on the thermodynamic database, Pandat software is used to calculate and obtain microstructure data of different aging temperatures (200°C, 250°C, 300°C, 350°C, 400°C, 420°C, 450°C, 480°C and 500°C) with Co content; the microstructure data includes the precipitate phase fraction and the solid solubility of Cu atoms; in step S2, the added Co content is controlled to be added to 2wt% at most; at each aging temperature, the added Co content is controlled to be added in a gradient of 0.005wt%-0.02wt%, such as 0.01wt%;

[0068] Step S3: Use the open source library pymoo to find the Pareto frontier of the precipitate phase fraction and the Cu atomic solubility (i.e., the point where both the precipitate phase fraction and the Cu atomic solubility are high) to obtain the target content of the copper alloy composition, i.e., Cu-2wt%Ni-0.5wt%Si-0.32wt%Co (see Figure 6-Figure 7 The screening component point 1 in the above formula is selected. At the same time, the target aging temperature is selected, i.e., 500°C. For details, see Figure 5-Figure 6The lower the aging temperature, the higher the maximum precipitated phase fraction and the higher the maximum Cu atomic solid solubility. However, a lower aging temperature will lead to a longer aging time and a slower precipitation process. At the same time, the Pareto front calculation results at 500°C are not much different from those at low temperatures. Therefore, in order to meet the actual industrial production efficiency, the aging temperature is determined to be 500°C.

[0069] Step S4, according to the target content of the copper alloy component and the target aging temperature obtained in step S3, an aging experiment is used to study the influence of different aging times on the hardness and electrical conductivity of the copper alloy, and then the target aging time is determined. Specifically, first, an alloy ingot with a composition of Cu-2wt%Ni-0.5wt%Si-0.32wt%Co is obtained by induction melting the alloy (wherein the selected raw material Cu purity is>99.95%, the raw material Ni purity is>99.95%, the raw material Co purity is>99.97%, and the raw material Si purity is>99.99%), and solid solution is performed at 1020°C for 1h, and water quenching is performed after solid solution. Then the ingot is cut into several discs with a diameter of Φ=18mm and a thickness of 2mm, and aged at 500°C for 0min, 60min, 180min and 300min, respectively, and air cooled after aging.

[0070] The conductivity of the copper alloy at different aging times (0min, 60min, 180min and 300min) was measured using a D60K-1201 digital metal conductivity meter, and the hardness of the copper alloy at different aging times (0min, 60min, 180min and 300min) was measured using a MicroMet 5104 microhardness tester, with a load of 100g and a loading time of 15s. The test results are shown in Table 1.

[0071] Table 1 Variation trend of hardness and electrical conductivity of quaternary Cu-2wt%Ni-0.5wt%Si-0.32wt%Co copper alloy at 500℃ with aging time in Example 1

[0072]

[0073] From the data in Table 1, it can be seen that the best performance of the Cu-2wt%Ni-0.5wt%Si-0.32wt%Co copper alloy designed by the design method of Example 1 is: Vickers hardness (HV) is 222.96HV, and the electrical conductivity is 46.38%IACS. Therefore, the target aging time of Example 1 is 60min.

[0074] Embodiment 2:

[0075] Different from Example 1, see Figure 5 and Figure 7, the target aging temperature is selected as 350°C. In step S4, the method for determining the target aging time is as follows. Specifically, first, an alloy ingot with a composition of Cu-2wt%Ni-0.5wt%Si-0.32wt%Co is obtained by induction melting the alloy, and solid solution is performed at 1020°C for 1h, followed by water quenching and cooling. Then the ingot is cut into several discs with a diameter of Φ=18mm and a thickness of 2mm, and aged at 350°C for 0min, 240min, 480min and 720min, respectively, and air cooled after aging.

[0076] The conductivity of the copper alloy at different aging times (0min, 240min, 480min and 720min) was measured using a D60K-1201 digital metal conductivity meter, and the hardness of the copper alloy at different aging times (0min, 240min, 480min and 720min) was measured using a MicroMet 5104 microhardness tester, with a load of 100g and a loading time of 15s. The test results are shown in Table 2.

[0077] Table 2 Variation trend of hardness and electrical conductivity of quaternary Cu-2wt%Ni-0.5wt%Si-0.32wt%Co copper alloy at 350℃ with aging time in Example 2

[0078]

[0079] From the data in Table 2, it can be seen that the best performance of the Cu-2wt%Ni-0.5wt%Si-0.32wt%Co copper alloy designed by the design method of Example 2 is: Vickers hardness (HV) is 216.68HV, and the electrical conductivity is 41.55%IACS. Therefore, the target aging time of Example 2 is 720min.

[0080] Embodiment 3:

[0081] The difference from Example 1 is that in step S2, the Ni content is controlled to decrease and the Co content is added, see Figure 9-10 , based on the thermodynamic database, Pandat software is used to calculate and obtain microstructure data of different aging temperatures (200°C, 250°C, 300°C, 350°C, 400°C, 420°C, 450°C, 480°C and 500°C) with Co content; the microstructure data includes the precipitate phase fraction and the solid solubility of Cu atoms; in step S2, the added Co content is controlled to be added to 2wt% at most; at each aging temperature, the added Co content is controlled to be added in a gradient of 0.005wt%-0.02wt%, such as 0.01wt%;

[0082] The open source library pymoo in step S3 is used to find the Pareto frontier of the precipitate phase fraction and the Cu atomic solubility (i.e., the point where both the precipitate phase fraction and the Cu atomic solubility are high at the same time) to obtain the target content of the copper alloy composition, i.e., Cu-1.48wt%Ni-0.5wt%Si-0.52wt%Co (see Figure 9-10 The screening component point 2 in the above); at the same time, the target aging temperature is selected, i.e., 500°C; for details, see Figure 8-Figure 9 The lower the aging temperature, the higher the maximum precipitated phase fraction and the higher the maximum Cu atomic solid solubility. However, a lower aging temperature will lead to a longer aging time and a slower precipitation process. At the same time, the Pareto front calculation results at 500°C are not much different from those at low temperatures. Therefore, in order to meet the actual industrial production efficiency, the aging temperature is determined to be 500°C.

[0083] Step S4, according to the target content of the copper alloy component and the target aging temperature obtained in step S3, an aging experiment is used to study the influence of different aging times on the hardness and electrical conductivity of the copper alloy, and then determine the target aging time. Specifically, first, an alloy ingot with a composition of Cu-1.48wt%Ni-0.5wt%Si-0.52wt%Co is obtained by induction melting the alloy, and solid solution is performed at 1020°C for 1h, and water quenching is performed after solid solution. Then the ingot is cut into several discs with a diameter of Φ=18mm and a thickness of 2mm, and aged at 500°C for 0min, 60min, 180min and 300min, respectively, and air cooled after aging.

[0084] The conductivity of the copper alloy at different aging times (0min, 60min, 180min and 300min) was measured using a D60K-1201 digital metal conductivity meter, and the hardness of the copper alloy at different aging times (0min, 60min, 180min and 300min) was measured using a MicroMet 5104 microhardness tester, with a load of 100g and a loading time of 15s. The test results are shown in Table 3.

[0085] Table 3 Variation trend of hardness and electrical conductivity of quaternary Cu-1.48wt%Ni-0.5wt%Si-0.52wt%Co copper alloy at 500℃ with aging time in Example 3

[0086]

[0087] From the data in Table 3, it can be seen that the best performance of the Cu-1.48wt%Ni-0.5wt%Si-0.52wt%Co copper alloy designed by the design method of Example 3 is: Vickers hardness (HV) is 234.24HV, and the electrical conductivity is 44.31%IACS. Therefore, the target aging time of Example 3 is 180min.

[0088] Embodiment 4:

[0089] Different from Example 3, see Figure 8 and Fig.10 , the target aging temperature is selected as 350°C. In step S4, the method for determining the target aging time is as follows. Specifically, first, an alloy ingot with a composition of Cu-1.48wt%Ni-0.5wt%Si-0.52wt%Co is obtained by induction melting the alloy, and solid solution is performed at 1020°C for 1h, followed by water quenching and cooling. Then the ingot is cut into several discs with a diameter of Φ=18mm and a thickness of 2mm, and aged at 350°C for 0min, 240min, 480min and 720min, respectively, and air cooled after aging.

[0090] The conductivity of the copper alloy at different aging times (0min, 240min, 480min and 720min) was measured using a D60K-1201 digital metal conductivity meter, and the hardness of the copper alloy at different aging times (0min, 240min, 480min and 720min) was measured using a MicroMet 5104 microhardness tester, with a load of 100g and a loading time of 15s. The test results are shown in Table 4.

[0091] Table 4 Variation trend of hardness and electrical conductivity of quaternary Cu-1.48wt%Ni-0.5wt%Si-0.52wt%Co copper alloy at 350℃ with aging time in Example 4

[0092]

[0093] From the data in Table 4, it can be seen that the best performance of the Cu-1.48wt%Ni-0.5wt%Si-0.52wt%Co copper alloy designed by the design method of Example 4 is: Vickers hardness (HV) is 173.78HV, and the electrical conductivity is 35.52%IACS. Therefore, the target aging time of Example 4 is 720min.

[0094] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. High hardness and high conductivity copper alloy composition and process design method, characterized in that: include: Step S1, establishing a thermodynamic database of quaternary Cu-Ni-Si-Co copper alloy; Step S2, on the basis of selecting Cu-Ni-Si commercial copper alloy, controlling the Cu content to decrease and adding the Co content, or controlling the Ni content to decrease and adding the Co content, based on the thermodynamic database, using Pandat software to calculate and obtain microstructure data that changes with the Co content at different aging temperatures; the microstructure data includes the precipitated phase fraction and the solid solubility of Cu atoms; Step S3, using the open source library pymoo to find the Pareto front of the precipitate phase fraction and the solid solubility of Cu atoms, so as to obtain the target content of the copper alloy component; at the same time, selecting the target aging temperature; Step S4: Based on the target content of the copper alloy components and the target aging temperature obtained in step S3, an aging experiment is performed to study the effects of different aging times on the hardness and electrical conductivity of the copper alloy, and then the target aging time is determined.

2. The high-hardness and high-conductivity copper alloy composition and process design method according to claim 1, characterized in that: In step S1, the thermodynamic database includes pure component thermodynamic data, binary system thermodynamic data and ternary system thermodynamic data; the pure component thermodynamic data include pure component Cu thermodynamic data, pure component Ni thermodynamic data, pure component Si thermodynamic data and pure component Co thermodynamic data; the binary system thermodynamic data include binary system Cu-Ni thermodynamic data, binary system Cu-Co thermodynamic data, binary system Cu-Si thermodynamic data, binary system Co-Ni thermodynamic data, binary system Co-Si thermodynamic data and binary system Ni-Si thermodynamic data; the ternary system thermodynamic data include ternary system Cu-Ni-Si thermodynamic data, ternary system Cu-Co-Si thermodynamic data and ternary system Cu-Co-Ni thermodynamic data.

3. The high-hardness and high-conductivity copper alloy composition and process design method according to claim 1, characterized in that: In step S2, the Cu—Ni—Si commercial copper alloy includes C70260 commercial copper alloy.

4. The high-hardness and high-conductivity copper alloy composition and process design method according to claim 1, characterized in that: In step S2, the added Co content is controlled to be added to 2wt% at most; at each aging temperature, the added Co content is controlled to be added in a gradient of 0.005wt%-0.02wt%.

5. The high-hardness and high-conductivity copper alloy composition and process design method according to claim 1, characterized in that: In step S2, the aging temperature ranges from 200 to 600°C.

6. The high-hardness and high-conductivity copper alloy composition and process design method according to claim 1, characterized in that: In step S3, the target content of the copper alloy components is as follows: 99.3wt%~95.9wt%Cu-0.5wt%~2.5wt%Ni-0.1wt%~0.6wt%Si-0.1wt%~1.0wt%Co.

7. The high-hardness and high-conductivity copper alloy composition and process design method according to claim 1, characterized in that: In step S3, the target aging temperature ranges from 350 to 600°C.

8. The high-hardness and high-conductivity copper alloy composition and process design method according to claim 1, characterized in that: In step S4, the target aging time is 1-12 hours.

9. A storage medium, characterized in that Computer program instructions are stored thereon, and when the computer program instructions are executed by a processor, the high-hardness and high-conductivity copper alloy composition and process design method as described in any one of claims 1 to 8 is implemented.

10. The device, characterized in that include: At least one processor, at least one memory and computer program instructions stored in the memory, when the computer program instructions are executed by the processor, implement the high hardness and high conductivity copper alloy composition and process design method as described in any one of claims 1 to 8.